Corrigendum to “The new modification of a solar still chamber with hollow glass: An experimental comparison between perpendicular and inline hollow glass configurations” [MESI Vol. 5, No. 2 (2025) pp 331-341]: Refers to: https://doi.org/10.31603/mesi.13238 - Eko Prasetyo Budiana; Muhamad Dwi Septiyanto; Satria Auliansyah; Naufal Rizky Sayyid; Indri Yaningsih; Syamsul Hadi (Universitas Muhammadiyah Magelang, 2026)
In the original article (https://doi.org/10.31603/mesi.13238), inaccuracies were identified in the reporting of productivity and thermal efficiency values cited from Reference [35] in Table 3 and the corresponding discussion in Section 4.2. Following a notification received by the Editorial Office and subsequent verification of the cited source, the authors agreed to revise the affected content. The corrections are presented below to ensure the accuracy and integrity of the published record.All corrections are provided in detail in the PDF file.Supplementary file S1: Letter to Editor